Ten years research activities in Earth observation at the Cyprus University of Technology - Hadjimitsis, Diofantos G.; Themistocleous, Kyriacos; Agapiou, Athos; Mamouri, Rodanthi-Elisavet; Nisantzi, Argyro; Papoutsa, Christiana; Tzouvaras, Marios; Neoclous, Kyriacos; Mettas, Christodoulos; Michaelides, Silas (My University, 2017)
This paper presents the achievements for the last 10 years of the Remote Sensing and Geo-Environment Laboratory of the Cyprus University of Technology in the Earth observation through the ERATOSTHENES Research Centre. Over the past 10 years, the Centre has secured competitive research funding from various sources, such as the European Commission, the Cyprus Research Promotion Foundation, as well as industrial partners, having participated either as a coordinator or as a partner in more than 60 research projects. The research activities of the Centre encompass remote sensing and GIS applications in the fields of Cultural Heritage, Agriculture, Water Resource Management, Environment, Infrastructure, Marine Spatial Planning, Atmospheric, Air Pollution and Coastal Applications, Natural Resource Management and Hazard Assessment. The aim of this paper is to map the existing activities and identify the future trends and goals of the Eratosthenes Research Centre for the next 15 years.
Keywords: ERATOSTHENES research centre; Opportunities; Remote sensing; Trends